Aproveitamento de água da chuva: um estudo qualitativo entre os principais sistemas - Teston, Andréa (2012)
The false idea water is an unlimited natural resource is supported by the water cycle, and therefore the issue has been neglected for too long. Nowadays, however, the water problem on the planet has exceeded the boundaries of countries suffering from shortages. It results in a constant search for programs of water conservation and use of alternative sources for human consumption, including the use of rainwater. This paper deals with the development of sustainable water issue: how the systematic destruction of the environment and population growth affect the quality and quantity of water available for human consumption. It also presents the larger watersheds of Brazil and Paraná with expectations about future water supply. At Metropolitan Region of Curitiba, it points to the need to explore new sources until 2025. This paper take a review of major environment and sustainable development world meetings and what their assumptions for the water issue. It presents the main public policies and the main laws and regulations governing about the issues of water conservation, with emphasis on use of rainwater. When it talks about water use in buildings, this paper try to clarify the main doubts of professionals about determining the system of rainwater must being used for a given demand. To do it, the systems of rainwater on the market are divided into components and analyzed separately on the parameters of durability, maintainability, efficiency, maintenance and cost. As a result, it attempts to develop guidelines in choosing the ideal system of rain according to the parameters required for a particular project.